(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores the crucial nexus between environmental education (EE) and sustainable development (SD) by investigating students' eco-consciousness in collaboration with the Worldwide Fund for Nature (WWF) Philippines. In an era characterized by escalating environmental concerns and the imperative for sustainable practices, understanding the role of education in fostering environmental sustainability is paramount. The research employed a quantitative method approach, using a survey to comprehensively examine students' attitudes, knowledge, and behaviors toward environmental issues and sustainable living practices. Drawing on a diverse sample of students across educational levels, the study found that at Saint Mary’s University, students have a high level of environmental awareness, eco-consciousness, and environmental stewardship. It was further affirmed that those three environmental concepts are intricately influencing one another. The profile variables of gender, age, type of high school they graduated from, and religion are not influential or predictive of their environmental awareness, eco-consciousness, and environmental stewardship. However, school, year level, and ethnicity are influential or predictive. Finally, Saint Mary’s University is fertile ground for environmental sustainability practices, as students have a high level of environmental awareness, eco-consciousness, and environmental stewardship, which are important dimensions of environmental sustainability. It was then recommended that its programs, projects, and activities be sustained and intensified to protect and conserve the environment.